(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: To our knowledge, no clinical study has previously been performed to investigate changes in the retinal ganglion cell complex (GCC) in diabetes mellitus (DM) patients differing in severity of diabetic polyneuropathy (DPN). Purpose: To identify changes in the GCC in patients with DPN differing in severity of the disease. Materials and Methods: A total of 575 patients (1150 eyes) with type 2 diabetes mellitus were included in the prospective analysis. DPN was diagnosed in 210 (36.5%) patients with DM. In addition to routine eye examination, retinal OCT was performed, and the macular GCC was assessed. Results: We found that the state of GCC in patients with DPN depends on the severity of the disease, and mean average GCC thicknesses in DM patients with N1A, N1B, and N3 stages DPN, were 8.4%, 8.6%, and 11.0% lower than in controls (95.8 ± 8.2 μm) (p < 0.001). In addition, in N1A, N1B, N2A, N2B and N3 stages DPN, mean focal loss volume (FLV) values were 8.4, 8.7, 14.1, 14.3, and 15.3 times, respectively, lower, whereas mean global loss volume (GLV) values were 119.1%, 124.8%, 231.3%, 239.6%, and 358.1%, respectively, higher, than in age-matched healthy controls. Conclusion: Retinal ganglion cell complex changes depend on the severity of diabetic polyneuropathy.